1959
DOI: 10.1021/ac60149a033
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Oxyacids of Phosphorus by Electrochromatography

Abstract: in this complex as nonnitrogenous unsaturated lactones. Crude preparations of aterrimin are being sold for use in poultry feeds.These examples illustrate the value of countercurrent distribution in separating widely different, biologically active materials from plant and animal sources. As information accumulates, its use will, no doubt, be expanded to serve many other purposes as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1959
1959
1973
1973

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…In addition to the previously published positions it was found that the P 4 -P 3 -P 4 -anion remains at the starting point, and that PS-O-P 4 -! * 4 migrates with nearly the same velocity as P 4 -P 4 ; salts of these anions were kindly supplied by Prof. S. OHASHI, and the positions agree with those found by him and his coworkers [18], In the separation zinc pyrophosphate is precipitated at the starting point [19]. This is necessary in order to obtain a satisfactory resolution of the remaining species, but it is -especially in the present case -dangerous since some polyphosphates might coprecipitate or migrate very slowly.…”
Section: Methodssupporting
confidence: 87%
“…In addition to the previously published positions it was found that the P 4 -P 3 -P 4 -anion remains at the starting point, and that PS-O-P 4 -! * 4 migrates with nearly the same velocity as P 4 -P 4 ; salts of these anions were kindly supplied by Prof. S. OHASHI, and the positions agree with those found by him and his coworkers [18], In the separation zinc pyrophosphate is precipitated at the starting point [19]. This is necessary in order to obtain a satisfactory resolution of the remaining species, but it is -especially in the present case -dangerous since some polyphosphates might coprecipitate or migrate very slowly.…”
Section: Methodssupporting
confidence: 87%
“…Besides Ρ 5 -Ο -Ρ 5 , which is precipitated at the starting point [3,11], only the anion corresponding to the irradiated salt is not carrier-free. The "carrier-free" activity peaks were almost symmetrical, and in most cases the distortion of the parent peak was modest; however, when the salt (NH 4 ) 5 P 3 O e was analysed, the colour reaction for phosphorus showed a peak front immediately after Ρ 5 -Ο -Ρ 6 -Ο -Ρ 5 and a tail covering most of the region ascribed to polyphosphates.…”
Section: Methodsmentioning
confidence: 99%
“…From 10 to 20 mg of the tagged material were dissolved in lactic acid 0.1 M, injected in Whatmann 3 MM paper l" Wide and subjected to electromigration with a gradient of 35 V/cm, for 1.5 to 2 hours according to the initial techniques of STRAIN and SATO [2,3,4].…”
Section: Identification Of the Tagged Materialsmentioning
confidence: 99%